Eocene Stratigraphic Sequences in the Prebetic of Alicante (SE Spain) and Their Correlation with Global Sea-Level and Climatic Curves - Crina Miclăuș; José Enrique Tent-Manclús; Josep Tosquella; Manuel Martín-Martín; Francisco Serrano (Journal of Marine Science and Engineering, 2025)
The Onil and Ibi sections (Prebetic Zone, Betic Cordillera: Alicante, SE Spain) record a late Ypresian (Cuisian) to early Lutetian (~51 to ~43 Myr) carbonate platform succession, dated using larger benthic foraminifera (LBF) and planktonic foraminifera. Seven field lithofacies (L1 to L7) and five thin-section microfacies (Mf1–Mf5) were identified, indicating inner- to mid-ramp environments (from seagrass meadows to Maërl-LBF-dominated) in warm-water and low-latitude conditions. A distinctive feature of these platforms is their dominance by LBF in association with rhodophyceae, contrasting with typical coral reef factories. We propose a novel carbonate production model, “TC-factory”, to describe these warm-temperate systems. Integrated field logging, drone imagery, and microfacies data allowed us to define a sequence stratigraphic framework comprising five lower-frequency sequences (LFS: ~2 Myr average duration), each of them nesting various numbers of high-frequency sequences (HFS: ~0.25 to ~1 Myr). The LFSs belong to a higher-rank sequence bounded by regional unconformities. The five LFSs only broadly match the upper Ypresian and lower Lutetian cycles in global eustatic curves (~51 to ~43 Myr), indicating that other regional or local controls were important. The number of HFSs being fewer than expected also suggests additional controls, such as local tectonics, erosion during lowstands, or carbonate production feedback.